Quantitative microbial risk assessment of a drinking water – wastewater cross-connection simulation. Issue 5 (1st September 2008) - Hurd, William W; Gibbs, Shawn G; Mena, Kristina D; Meckes, Mark C; Mota, Linda C; Green, Christopher F
Abstract : Quantitative microbial risk assessment is a useful way to predict the incidence of infection and illness within a community following exposure to pathogens. We used this risk assessment technique to determine the expected number of Salmonella infections and illnesses resulting from a drinking water - wastewater cross-connection incident using data generated from a distribution system simulator study and compared our results to a reported cross-contamination event that occurred in Pineville, Louisiana in 2000. Probabilities of infection and illness were estimated for different exposure scenarios representing different Salmonella concentrations and the characteristic varied attack rates for waterborne Salmonella . Risks of Salmonella infection range from 10% after a 1 day exposure (assuming the lower bound Salmonella concentration) to a 1-log greater risk of infection for all other scenarios, with risks of infection approximately 99% for 30 and 90 day exposure durations.